2021
DOI: 10.1080/2090598x.2021.1932125
|View full text |Cite
|
Sign up to set email alerts
|

Can high-dose tranexamic acid have a role during transurethral resection of the prostate in large prostates? A randomised controlled trial

Abstract: Can high-dose tranexamic acid have a role during transurethral resection of the prostate in large prostates? A randomised controlled trial, Arab Journal of Urology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…For example, TXA seems to decrease surgical time during TURP. 38 , 39 This advantage is desirable to decrease the potential complications, like thromboembolism events, blood loss, and effects due to irrigating fluid absorption, especially in oncological patients.…”
Section: Clinical Usage and Efficacy Of Tranexamic Acid In Oncologic ...mentioning
confidence: 99%
“…For example, TXA seems to decrease surgical time during TURP. 38 , 39 This advantage is desirable to decrease the potential complications, like thromboembolism events, blood loss, and effects due to irrigating fluid absorption, especially in oncological patients.…”
Section: Clinical Usage and Efficacy Of Tranexamic Acid In Oncologic ...mentioning
confidence: 99%
“…Also, the mean operative time of the TXA group was significantly lower compared to placebo (68.45 vs. 87.62 min, P < 0.001) [ 10 ]. Also, Samir et al [ 17 ] reported that high-dose TXA was effective in controlling blood loss during bipolar TURP in patients with large prostates. However, no study has been conducted on the use of TXA in the irrigation fluid during TURP.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this meta-analysis included 13 RCTs. [7][8][9][10][11][12][13][14][15][16][17][18][19] One trial included patients from 2 hospitals, and the other 12 trials were all conducted in a single hospital. Seven trials targeted patients undergoing percutaneous nephrolithotomy, [8,[12][13][14][15]17,18] 5 focused on prostatectomy, [7,9,10,16,19] and 1 investigated transurethral resection of the prostate/bladder tumor.…”
Section: Characteristics Of Enrolled Trialsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] One trial included patients from 2 hospitals, and the other 12 trials were all conducted in a single hospital. Seven trials targeted patients undergoing percutaneous nephrolithotomy, [8,[12][13][14][15]17,18] 5 focused on prostatectomy, [7,9,10,16,19] and 1 investigated transurethral resection of the prostate/bladder tumor. [11] In all 13 trials, TXA was administered before surgery, and patients in 8 trials also received postoperative TXA.…”
Section: Characteristics Of Enrolled Trialsmentioning
confidence: 99%
See 1 more Smart Citation